AFTER BIOPOLITICS – TRUE DEMOCRACY AS 21ST CENTURY „LIFEWORLD“ - Koljevic Griffith, Bogdana (Serbian political thought, 2023)
In this article the author, firstly, considers different aspects of contemporary neoliberalism as biopolitics, especially reflecting the issue of cryptodemocracy in the end of 20th as well as in the first decades of 21st century. Or, more precisely, beginning from Foucault’s articulation of biopolitics as both regulation and control of population, the issue of multiple forms of “liberal democracy” in neoliberalism and poststructualism is critically addressed. In this light, divergent forms of “liberal democracy” as procedural i.e., formal democracy which appears as the primary condition of possibility for biopolitical neototalitarianism are analyzed. This neototalitarianism of the West i.e., of Pax Americana, which simultaneously includes the project of the EU, is primarily manifested through numerous contemporary phenomena of biopolitics – from “humanitarian interventionism” to “wars against terrorism” and measures taken against COVID 19. The common ground for all phenomena is traced back to the “friend-enemy” distinction, as well as to politization of the body as the conditions which enabled de(con)struction of both homo politicus and democracy. It is emphasized that the structural binary opposition is one between East and West and that, moreover, biopolitical neototalitarianism targets precisely the otherness of the East which it perceives as unbearable.  In the second part of the article, it is argued that reaffirmation of polis requires a theory and practice of “true democracy” – as “democracy of content” – which is conceptually different from any form of “formal democracy”. Furthermore, true democracy is, first and foremost, articulated as politics of the local i.e., as both politics of place and politics of time. Therefore, in opposition to “neoliberal presentism” and “the end of history” a return to democracy falls in one with rebirth of history. Transcendence of time and immanence of space constitute the framework for comprehending knowledge as remembrance which, in the next step, enables the foundation of a new paideia for the 21st century. Or, in other words, special relevance of education for true democracy - as well as for the structural relation between the political and the normative element – is emphasized. In such a way, the author at the same time reflects upon the necessity of culture for true democracy and formation of the polis because culture – which always comes in plural – is the sine qua non not only for politics and ethics but for the possibility of civilization. The potential for realization of political subjectivity and sovereignty is then presented in the form of true democracy as self-determination of the people. In conclusion, this process is also marked by forming of specific Sittlickeit i.e., “democracy of content” is manifested through multiplicity of forms of “lifeworld” which come forth from history, tradition, and high culture. In such a way, the life of the people as democratic life par excellence, with all its particularities, opens the space for horizons of new humanism in the 21st century that is also constituted as the final foundation for restauration of homo politicus.
Keywords: neoliberalism, biopolitics, political subjectivity, sovereignty, true democrple, lifeworld, humanism.